Rancang Bangun Aplikasi Messaging Berbasis Voice Interaction Bagi Penderita Tunanetra Pada Sistem Operasi Android - Leo Tiofan Justicia; Herman Tolle; Faizatul Amalia (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Smartphone technologies that exist today, comes to offer a number of easines for the communications process that is performed by humans. Through the use of smartphone technology, humans are able to communicate in realtime communication without distance limitations. However, people with visual impairment actually confront it with a number of differences. People with visual impairment is a disability category who have physical limitations for work that requires visualization capabilities. So with these limitations, they can't operate a smartphone to communicate with others. Through this research, developed a voice-interaction-based messaging application to help people with visual impairments to communicate with others using a smartphone. This application allows users to control the application by touch or voice commands. Users will receive feedbacks in the form of speech output for each given voice command. Based on MOS (Mean Opinion Score) Testing that has been done, obtained MOS value by 3.7. It means, the average user stating that the voice-interaction service that contained in the application has a good quality.